Sufficient conditions to stabilize time‐varying nonlinear sampled‐data systems via approximation. (12th May 2016) - Ling, Qiang; Yan, Zhe; Ji, Haibo; Wang, Yong; Xie, Yongchun
Summary: This paper investigates the problem of stabilizing a time‐varying nonlinear sampled‐data system based on its approximate models. Given a time‐varying nonlinear sampled‐data system, we make use of the approximate models of the system at each sampling instant to build a time‐varying approximate model with which an appropriate controller is designed. This paper provides some sufficient conditions under which a controller stabilizing the approximate models can also stabilize the exact sampled‐data system under any sufficiently small sampling period. With this method, we do not need to compute the complicated exact discrete‐time model of the concerned system and significantly simplify the controller design. The major contribution of this method lies in extending the available results regarding the time‐invariant sampled‐data systems to the time‐varying case. Moreover, this method enables us to analyze the influence of the precision of approximate models on the system performance. Copyright © 2016 John Wiley & Sons, Ltd.